Reliability of a Smooth Pursuit Eye-Tracking System (EyeGuide Focus) in Healthy Adolescents and Adults - Alan J. Pearce; Ed Daly; Lisa Ryan; Doug King (Journal of Functional Morphology and Kinesiology, 2023)
Mild traumatic brain injury (mTBI) is the most common brain injury, seen in sports, fall, vehicle, or workplace injuries. Concussion is the most common type of mTBI. Assessment of impairments from concussion is evolving, with oculomotor testing suggested as a key component in a multimodality diagnostic protocol. The aim of this study was to evaluate the reliability of one eye-tracking system, the EyeGuide Focus. A group of 75 healthy adolescent and adult participants (adolescents: n = 28; female = 11, male = 17, mean age 16.5 ± 1.4 years; adults n = 47; female = 22; male = 25, mean age 26.7 ± 7.0 years) completed three repetitions of the EyeGuide Focus within one session. Intraclass correlation coefficient (ICC) analysis showed the EyeGuide Focus had overall good reliability (ICC 0.79, 95%CI: 0.70, 0.86). However, a familiarization effect showing improvements in subsequent trials 2 (9.7%) and 3 (8.1%) was noticeable in both cohorts (p < 0.001) with adolescent participants showing greater familiarization effects than adults (21.7% vs. 13.1%). No differences were observed between sexes (p = 0.69). Overall, this is the first study to address the concern regarding a lack of published reliability studies for the EyeGuide Focus. Results showed good reliability, suggesting that oculomotor pursuits should be part of a multimodality assessment protocol, but the observation of familiarization effects suggests that smooth-pursuit testing using this device has the potential to provide a biologically-based interpretation of the maturation of the oculomotor system, as well as its relationship to multiple brain regions in both health and injury.